2015
DOI: 10.5296/csbm.v2i1.6809
|View full text |Cite
|
Sign up to set email alerts
|

Female Entrepreneurship in Kenya: How do Female Micro-Entrepreneurs Learn to be Entrepreneurial?

Abstract: There is renewed interest in female entrepreneurship as policy makers recognize the importance of social inclusiveness in economic development. Women's involvement in entrepreneurship is applauded as a necessary precursor to economic growth of developing nations despite women under-representation among business owners. Many factors have been blamed for this under-representation among them, socialisation and lack of motivation in choosing entrepreneurship as a career option. In Kenya, women entrepreneurs have l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Also, ILO (2019) confirms that imparting transferable skills to women workers through approaches such as activity-based learning and peer collaboration mitigate them from being displaced by robotic automation and artificial intelligence. However, Mutuku et al (2015) observed that 76.9 percent of female entrepreneurs went into business without prior business skills and rarely actively searched for entrepreneurial knowledge or skills. Cusolito and Maloney (2018) argue that more than the basic education, technological expertise, managerial capabilities, and forbearance for risk are the crux to successful entrepreneurship.…”
Section: Transferable Skills and Employmentmentioning
confidence: 99%
“…Also, ILO (2019) confirms that imparting transferable skills to women workers through approaches such as activity-based learning and peer collaboration mitigate them from being displaced by robotic automation and artificial intelligence. However, Mutuku et al (2015) observed that 76.9 percent of female entrepreneurs went into business without prior business skills and rarely actively searched for entrepreneurial knowledge or skills. Cusolito and Maloney (2018) argue that more than the basic education, technological expertise, managerial capabilities, and forbearance for risk are the crux to successful entrepreneurship.…”
Section: Transferable Skills and Employmentmentioning
confidence: 99%
“…Entrepreneurship has been shown to contribute to the world's workforce profitability, and as a result, women are major beneficiaries through the improvement of their livelihoods and financial status (Mulu-Mutuku et al, 2015). Women empowerment has led to a positive rise in more women engaging in entrepreneurial activities (Wambui & Muathe, 2021).…”
Section: Entrepreneurs Networkmentioning
confidence: 99%
“…Women-owned enterprises tend to be generally smaller than enterprises owned by men. Majority of women's enterprises in Kenya remain small, showing no signs of growth with most exiting the market at early ages (Mutuku, Wanga, & Olubandwa, 2015). The Kenyan government runs various empowerment programs and creates awareness amongst the youth, women, and persons with disabilities through various platforms.…”
Section: Introductionmentioning
confidence: 99%